ANALISIS NILAI TAMBAH PADA INDUSTRI KERAJINAN PAKAIAN BORDIR DI DESA SERI TANJUNG - Saadah Yuliana; Suhel Suhel; Muhammad Isnadhi (Jurnal Ekonomi Pembangunan, 2004)
The title of this research is "Value Added and Analysis of Pakaian Bordir Industry in Seri Tanjung Village". This research is aimed to know the value added that has been resulted by the industry v/ pakaian bordir and how capital and wages factor increased the production of pakaian hordir in Seri Tanjung village.This research has been done in Seri Tanjung village, which has taken forty four samples, which are considered to represent the pakaian bordir industries in that village.Â  Keyword: Value added, capital, wages, pakaian bordir